DISTRIBUSI PEMBANGUNAN EKONOMI SEKTORAL DI PROPINSI JAWA TIMUR - Suparta, I Made (Program Doktor Ilmu Ekonomi, 2008)
The purpose of this research is to study distribution of economic development among economic sectors inEastJavaProvince. The data analisys technique uses dispersion analysis with variance method. In the period of 2002-2006, result of the variance analysis shows that distribution of economic development among economic sectors inEastJavaProvinceis getting unbalanced.Â Keywords: distribution, economic sector, development.